Enterobacteriaceae dan Personel Hygiene Ibu Terhadap Kejadian Diare Anak 5 Tahun di Kecamatan Ratu Samban Kota Bengkulu - Halimatussa'diah Halimatussa'diah; Ervan Ervan; Agung Riyadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Diarrheal disease is one of the environment-based diseases and is closely related to personal hygiene conditions and the presence of Enterobacteriaceae in food. Diarrheal diseases can also spread from person to person, exacerbated by poor personal hygiene. Food is another major cause of diarrhea when prepared or stored in unhygienic conditions. Unsafe storage and handling of household water is also an important risk factor. Personal habits that do not want to wash hands with soap before carrying out their activities, as well as other behaviors that do not reflect a healthy lifestyle can cause diarrhea. This study aims to determine the relationship between enterobacteriaceae in food and maternal personal hygiene with the incidence of diarrhea in children less than 5 years old in Ratu Samban District, Bengkulu City. This research is an analytic survey research with a cross-sectional approach. From the research data, statistical test results were obtained with chi square, there was no significant relationship between Enterobacteraiceae in food and maternal hygiene personnel with the incidence of diarrhea in children less than 5 years old in Ratu Samban District, Bengkulu City in 2022 where the p value > from 0.05.